Biossensor de glicose baseado na imobilização da glicose oxidase em nanofibras de óxido de zinco - Oliveira, Vitor Hugo Batista de (2019)
Diabetes is a chronic disease that causes one death every 10 seconds throughout the world. In view of this scenario, zinc oxide (ZnO) nanofibers were synthesized by electrospinning technique followed by thermal treatment for use as glucose biosensors for demonstrating good chemical, physical and biological properties. The composite nanofibers were obtained from a 2: 1, 1: 1 and 1: 2 aqueous solution of vinyl alcohol (PVA) and zinc acetate (AcZn). Studies have demonstrated the effects of the 2: 1, 1: 1 and 1: 2 mass concentration of zinc acetate (PVA: AcZn) and calcination temperature for 2 hours at (500 ° C, 600 ° C and 700 ° C) on morphology and structure of composite nanofibres and of ZnO. The nanofibers obtained from the 1: 1 condition (PVA: AcZn) were chosen for the manufacture of an enzymatic glucose biosensor, because remaining the fiber format even after calcination at 600 ° C. This is of paramount importance for application in glucose biosensors. The ZnO nanofibers were then used to immobilize the glucose oxidase enzyme by forming a composite on the surface of the glassy carbon electrode for glucose detection in PBS pH 7.2. The developed enzymatic biosensor (CGE / ZnO / GOx) showed excellent electrochemical properties in relation to the pure CGE electrode and CGE / ZnO. In the presence of 1.67 mmol / L glucose the CGE / ZnO / GOx electrode increased the glucose oxidation current by about 60% relative to PBS. Stability study showed the high bioactivity and stability of the immobilized enzyme in the ZnO nanofiber, because it retained about 75% of the initial peak current even after 300 cycles of cyclic voltammetry. These results suggest that the electrode modified with the ZnO and GOx nanofibers exhibits high potential for application as a glucose biosensor.